2016
DOI: 10.3390/cosmetics3030029
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergy to Preservatives—Is the European Commission a Commendable Risk Manager?

Abstract: Abstract:Although preservatives are necessary to prevent deterioration by microbial growth in cosmetic products, daily skin contact with preserved cosmetic products may cause a preservative contact allergy. Only preservatives with sufficient pre-market risk assessment, presumably being safe for the consumer from a public health point of view, are permitted for use in cosmetic products in the European Union. Notwithstanding the efforts by the European Commission (EC) to avoid epidemics of contact allergy, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The process of communicating the evidence of an emerging epidemic from the scientific community to the EC has not functioned optimally to protect the consumers from MI, delayed partly by neglect of the EC and opposing evidence by Cosmetics Europe 14,23 . It has previously been suggested that preservatives be adopted in Annex V on a time‐limited entry, thus requiring reevaluation after a certain time period 24 . It is not unreasonable to suggest that this would have limited the magnitude of the epidemic of contact allergy to MI.…”
Section: Discussionmentioning
confidence: 99%
“…The process of communicating the evidence of an emerging epidemic from the scientific community to the EC has not functioned optimally to protect the consumers from MI, delayed partly by neglect of the EC and opposing evidence by Cosmetics Europe 14,23 . It has previously been suggested that preservatives be adopted in Annex V on a time‐limited entry, thus requiring reevaluation after a certain time period 24 . It is not unreasonable to suggest that this would have limited the magnitude of the epidemic of contact allergy to MI.…”
Section: Discussionmentioning
confidence: 99%
“…Such products may consist of various hazardous ingredients that may cause skin and respiratory irritation. For example, exposure to preservatives, which used as antimicrobial ingredients, may lead to skin sensitization and allergic contact dermatitis (Schwensen and Thyssen, 2016). Meanwhile, inhalation of household disinfectants may cause serious lung injuries and even lead to fatality (Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%